2023
DOI: 10.1002/jclp.23533
|View full text |Cite
|
Sign up to set email alerts
|

Off track or on? Associations of positive and negative life events with the continuation versus cessation of repetitive adolescent nonsuicidal self‐injury

Abstract: ObjectiveThis study examined how patterns of repetitive (≥5 instances) nonsuicidal self‐injury (NSSI) associate with measures of resilience and life events retrospectively reported to have occurred within the last year, 1 to <5 years ago, and 5 to <10 years ago.MethodLife events reported by 557 young adults (mean [SD] age 25.3 [0.68]; 59.2% women) were classified as positive, negative, or profoundly negative based on their relationship to participants' mental health and well‐being. We subsequently examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 76 publications
(162 reference statements)
0
1
0
Order By: Relevance
“…The integrated theoretical model of NSSI suggests that stressful life events are significant triggers for NSSI [8]. Consistent evidence also indicates that adolescents engage in NSSI more frequently after experiencing stressful life events [9][10][11]. For example, a prospective study of 529 adolescents found that stressful life events significantly predicted adolescent NSSI one year later [12].…”
Section: Introductionmentioning
confidence: 93%
“…The integrated theoretical model of NSSI suggests that stressful life events are significant triggers for NSSI [8]. Consistent evidence also indicates that adolescents engage in NSSI more frequently after experiencing stressful life events [9][10][11]. For example, a prospective study of 529 adolescents found that stressful life events significantly predicted adolescent NSSI one year later [12].…”
Section: Introductionmentioning
confidence: 93%